Investigating Pregnancy Outcomes After Abnormal Cell‐Free DNA Test Results. Issue 4 (24th January 2018) - Lu, Jessica; Saller, Devereux N.; Fraer, Luanne M.; Chen, Beatrice A.
Abstract: Cell‐free DNA (cfDNA) testing has increased sensitivity and specificity compared to other prenatal screening methods, but invasive diagnostic testing (IDT) is recommended for confirmation. We performed a retrospective chart review of 39 women with abnormal cfDNA results between March 2012 and September 2015 at an urban academic hospital to evaluate patient choice and pregnancy outcomes. We analyzed data using descriptive statistics, Fisher's exact tests, and Wilcoxon rank‐sum tests. Median maternal age was 36.0 years [interquartile range (IQR) 31, 39]; 64.1% of women (25/39) were advanced maternal age and 69.2% (27/39) had abnormal ultrasounds. Median gestational age at time of cfDNA testing was 18 3/7 weeks [IQR 12 2/7, 20 5/7]. cfDNA results included trisomy 21 (89.7%, 35/39), trisomy 18 (7.7%, 3/39), and both trisomy 21/monosomy X (2.6%, 1/39). Of 39 women, 22 (56.4%) continued and 10 (25.6%) terminated the pregnancy; six (15.4%) had fetal demises, and one was lost to follow‐up. Of women continuing their pregnancies, 54.6% (12/22) declined further genetic counseling, and 77.3% (17/22) declined IDT. Only 14 women pursued IDT; not pursuing IDT was associated with continuing the pregnancy (Fisher's exact test, p  = .001). All women terminating their pregnancy (90.0%, 9/10) pursued IDT or had major anomalies on ultrasound, suggesting that women considering termination undergo more confirmatory tests or already have high suspicion for an abnormal pregnancy.